The professional protection officer : practical security strategies and emerging trends (Butterworth-Heinemann, 2010)
The Professional Protection Officer, the succesor to our Protection Officer Training Manual, is a comprehensive training guide and instructional text that covers all of the subjects essential to the effective training of protective officers. This material, now in itseighth edition, has been class-tested for many years and has been the training manual for the International Foundation for Protection Officers (IFPO) since 1988. The new book contains brand new chapters on the most significant issues facing the protection officer today, including Central Alarm Stations, Communications, Survei.